Adverse reactions of botulinum toxin type A for treating strabismus in children - E.E. Sidorenko; I.A. Ostanina; K.N.M. Rosel’o; D.V. Migel; E.I. Sidorenko (РМЖ "Клиническая офтальмология")
E.E. Sidorenko1,2, I.A. Ostanina2, K.N.M. Rosel’o1, D.V. Migel’1,2, E.I. Sidorenko1 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2V.F. Voino-Yasenetskiy Scientific and Practical Center for Specialized Medical Care   for Children, Moscow, Russian Federation Background: the use of botulinum toxin type A (BTA) in ophthalmology for extraocular disorders in children and adults became possible was pioneered by A. Scott in the 1980s. Lack of experience and understudied risks of this treatment modality in Russia prevent the introduction of chemodenervation into daily ophthalmic practice. In addition, several adverse reactions of BTA were reported. Therefore, these adverse reactions should be considered when choosing this treatment in adults and children. Aim: to assess the efficiency and adverse reactions of BTA when treating strabismus in children. Patients and Methods: 212 children (424 eyes) aged seven months to 15 years with estab-lished strabismus were enrolled. Visual fixation and acuity were measured before BTA injection. BTA was injected in horizontal extraocular muscles (average dose 3.40 U). Results: the average angle of strabismus was 33.28±12.96°, the average angle of eso-tropia was 33.69±12.86°, the average angle of exotropia was 31.50±13.41°. Neutralization of strabismus angle was achieved in 92.2%, a reduction in strabismus angle was reported in 7.8%. In total, 288 procedures were performed. 76 patients (35.85%) required re-surgeries. In most cases, re-chemodenervation was performed in children with a strabismus angle >25° (Hirschberg test). Adverse reactions of chemodenervation were blepharoptosis (2.83%), hypereffect (17.45%), conjunctival redness, and edema at the injection sites. These adverse reactions were self-limited, no specific treatment was needed. Conclusion: chemodenervation by BTA injection in hyperfunctional extraocular muscles is a highly effective, non-traumatic, and safe treatment for strabismus in children. All adverse reactions identified by our study were transient. Keywords: botulinum toxin type A, postoperative complications, strabismus, nystagmus, extraocular disorders, chemodenervation. For citation: Sidorenko E.E., Ostanina I.A., Rosel’o K.N.M. et al. Adverse reactions of botulinum toxin type A for treating strabismus in children. Russian Journal of Clinical Ophthalmology. 2022;22(2):145–148 (in Russ.). DOI: 10.32364/2311-7729-2022-22-2-145-148.